Milk and dairy products as functional foods - Kanekanian, Ara (Wiley Blackwell : SDT, 2014)
"This book draws together a wealth of information regarding the functional health benefits of milk and dairy products"-- Provided by publisher.
Keywords: mlékařství; mléko; mléčné výrobky; nutraceutika; dairying; milk; dairy products; nutraceuticals; elektronické knihy; electronic books